PJMHS 2022
DOI: 10.53350/pjmhs22169104
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Teacher centered and Student Centered Medical Education Approach: An experimental research

Abstract: Aim: To investigate the comparison between teacher centered and Student centered medical education approach among multiple medical and dental institutes of Lahore. Methods: A thorough investigation was done by collecting data on results of students given Teacher centered medical education and Student centered medical education. Students of each class were divided into 5 groups and given tasks of presenting on given topics and individual students’ participation was encouraged in each group. Results: The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…According to the research conducted in Kasturba Medical College, it was found that the faculty felt that they didn't give the required time to their subordinates as they were preoccupied due to their hectic schedules 16 . Increase in the number of faculty members who are skilled and trained research coordinators can assist in overcoming the difficulty in finding proficient research mentors 17,18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research conducted in Kasturba Medical College, it was found that the faculty felt that they didn't give the required time to their subordinates as they were preoccupied due to their hectic schedules 16 . Increase in the number of faculty members who are skilled and trained research coordinators can assist in overcoming the difficulty in finding proficient research mentors 17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in multiple medical and dental colleges of Lahore states that teacher centric method of conveying knowledge are getting outdated 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Yet, researchers indicated that students’ performance in student-centered STEM courses is higher than that in teacher-centered education. For instance, Rathore and Colleagues (2022) compared 362 medical and dental students’ course performance in a teacher-centered course and a student-centered course. Results of their study revealed that in the teacher-centered class, 20% of the class scored above 80 marks, 78% of the class scored between 60 and 80, and 2% scored less than 60 marks.…”
Section: Literature Reviewmentioning
confidence: 99%